The Ethics of The Tripartite Tractate (NHC I, 5) A Study of Determinism and Early Christian Philosophy of Ethics - Linjamaa, Paul (Nag Hammadi and Manichaean Studies, 2019)
In The Ethics of The Tripartite Tractate (NHC I, 5), Paul Linjamaa explores the theoretical foundations and practical implications of the ethics in the longest Valentinian text extant today. As such, it is one of the first serious explorations of early Christian determinism.; Readership: All interested in Valentinianism, early Christian ethics and the development of early Christian theory of the human will.